2022
DOI: 10.1155/2022/6269921
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception of Informed Consent and Its Associated Factors among Surgical Patients Attending Public Hospitals in Dessie City Administration, Northeast Ethiopia

Abstract: Background. Poor perception of informed consent compromises patients’ autonomy and self-determination; as a result, they feel powerless and unaccountable for their treatment. This study aimed to assess patients’ perception of informed consent and its associated factors among surgical patients attending public hospitals in Dessie City Administration, Northeast Ethiopia. Methods. Facility-based cross-sectional study was conducted on 422 surgical patients. A systematic sampling technique was used to select the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…For ethical and legal reasons the duty to obtain patients’ consent typically rests on the physician. Yet, several studies9 40 44–46 54 55 in this review reported a range of healthcare providers obtaining SIC, including nurses or midwives not involved in the surgical procedure and not trained in SIC counselling 52…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…For ethical and legal reasons the duty to obtain patients’ consent typically rests on the physician. Yet, several studies9 40 44–46 54 55 in this review reported a range of healthcare providers obtaining SIC, including nurses or midwives not involved in the surgical procedure and not trained in SIC counselling 52…”
Section: Resultsmentioning
confidence: 93%
“…In general, the most frequently explored implications of SIC were patients’ understanding of the procedure and risks involved36–47 (including recall of information as proxy27 48 49), autonomy in decision-making9 27 36 37 40 42 43 47 49–51 and satisfaction with the process 21 27 41 44–46 49 52–55…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is in line with the finding in Dessie. 31 Reducing the language barrier might be that providing health information in understandable language might increase interaction and communication between health care providers. In addition, women can understand the situation.…”
Section: Discussionmentioning
confidence: 99%